Empirical Validation of an Ecosystem Service Map Developed From Ecological Principles and Biophysical Parameters - Townsend, Michael; Lohrer, Andrew M. (Frontiers in Marine Science, 2019)
Mapping ecosystem services in marine systems is difficult due to a lack of underpinning ecological data. The Ecological Principles Approach (EPA) was developed to link simple summary statements on how ecosystems function to ecosystem services and was further advanced into a mapping technique by aligning and weighting commonly available spatial datasets to generate maps of specific services. The objective of the present investigation was to validate a predicted map of biogenic habitat provision with empirical ground-truthed data. A survey was undertaken to assess the biogenic habitat structure at 56 sites in the Hauraki Gulf, New Zealand. Information on benthic biogenic structure was ranked from 1-5 relating to a combination of height and complexity. Rank groups were assessed for differences in predicted levels of service and the accuracy of supporting data. We found high agreement between the empirical observations and the model predictions: in areas predicted by the approach to have the highest levels of biogenic habitat complexity the habitat was typified by complex rocky reef communities and macroalgal forests. We showed that ecosystem services can be accurately mapped in marine systems at low cost and with modest data requirements, which further enhances the utility of this approach.